Hysterectomy: recent trends & alternatives: an overview - Chowdhury, Shahanara; Noor, Sirajun; Ferdous, Afroza (Journal of Chittagong Medical College Teachers’ Association, 2011)
Keywords: hysterectomy; laparoscopy; recent trends DOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9115 JCMCTA 2011; 22(1): 54-60